Development and validation of the Chinese surgical inpatient satisfaction and comfort questionnaire. Issue 52 (30th December 2021) - Liu, Bolin; Liu, Shujuan; Zheng, Tao; Wang, Yuan; Cao, Baohua; Wang, Zhiling; Yu, Lijun; Zhang, Na; Zhao, Binfang; Lu, Dan; Chen, Lei; Ma, Tao; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Patient feedback can provide insights to assess and improve the quality of healthcare. This study aimed to develop a measure of surgical inpatient satisfaction and comfort and examine its acceptability, validity, and reliability among discharged surgical patients. This multicenter, descriptive, cross-sectional study was conducted at three tertiary hospitals in Shaanxi Province, China. A random sample of patients admitted to the surgical inpatient departments of the three hospitals between November and December 2018 was recruited. An analysis was conducted on the acceptability, validity, and reliability of a newly developed measure of satisfaction with surgical inpatient services. A total of 1582 out of 1805 (87.6%) eligible patients completed the questionnaire (average time taken = 17.1 ± 10.3 minutes), which indicated high acceptability. Sociodemographic differences between the participants and non-participants were not significant. Using factor analysis, the following 7 dimensions (number of items: 65, variance explained: 68.0%) were identified: medical care (19 items), nursing care (15 items), environment and logistics (11 items), postoperative and hospitalization experiences (11 items), feeling nervous and afraid (4 items), operating room services (3 items), and visiting (2 items). The latent structure of the assessment was examined and validated using exploratory and confirmatory factor analyses, respectively. All item loadings were >0.4. All dimensions demonstrated satisfactory internal consistency (Cronbach's alphas = 0.83–0.96) and test-retest reliability (intra-class correlation coefficients = 0.77–0.96). The Chinese Surgical Inpatient Satisfaction and Comfort Questionnaire has strong psychometric properties and can be used to assess patient satisfaction with public hospital surgical inpatient services in China. A distinguishing feature of this questionnaire is the inclusion of a subscale that assesses comfort as a dimension of patient satisfaction. Such instruments can be used to identify the factors that should be addressed to improve the quality of patient care. Further research is needed to determine the role of assessment in quality improvement.